(untitled) (Majalah Ilmiah UNIKOM, 2021)
Multimedia can collaborate between text, sound, photo, animation, and video elements through computer devices that are digitally manipulated by conveying information, and controlled interactively. Interactive multimedia in learning can solve learning problems in the digital age to trigger intelligence in students’ thinking. The purpose of this research is to test the theory of interactive multimedia elements used in the Interactive CD of the Solar System Physics Lab as a supplement to electronic learning. This research method was carried out using a descriptive qualitative approach regarding the results of the study of the interactive multimedia design structure on the Interactive CD of the Solar System Physics Lab. The results of this study will determine the structure of an interactive multimedia design that can be used as a reference and reference for teachers and interactive multimedia developers. Key Words : Digital, e-learning, interactive, learning, multimedia